Target position and trajectory measurements by videogrammetry - Hobbs, Stephen (Cranfield University, 2003)
This report documents the algorithms, data processing and software for the video photogrammetry ("videogrammetry") system developed at Cranfield University. Cranfield's system has been used successfully since 1999 on a range of measurement projects. Videogrammetry typically uses two video cameras to film the motion of target objects in stereo, and then with suitable image processing and data analysis the targets' 3d trajectories are measured to good precision. The main features of the Cranfield systems are that it is based on consumer electronics devices (e.g. digital camcorders and PC's), and that it is designed as an experimental tool. Using consumer electronics provides good performance at low cost. Its experimental character means that an expert user is required, but does allow great flexibility. Current system performance derives from the image resolution of 1 mrad per pixel over a field of view 720 by 576 pixels, and a frame rate of 25 Hz. Two areas of work are described: (1) the mathematical models and algorithms used for calibration, position measurement and trajectory extraction, and (2) the software tools written to manipulate images and process the data. The model of the imaging system can be adapted for a wide range of applications, and is explicitly developed in this report for a single camera position and pose calibration, a two-camera system calibration, and a measurement sys- tem using two or more cameras (either the general non-linear case or a linear approximation). The image calibration (which converts image coordinates to geometrical angles of inclination and azimuth) is based on a 3rd order polyno- mial and achieves an accuracy equivalent to better than 1 pixel. Trajectories are obtained by either labelling targets or using kinematic rules. Two programs (AVI1 and mfitvid) have been written for the videogrammetry system and are described in outline (for a user and to support future development). Commercial software provides the more general functions required by the system. Experience with the videogrammetry system over a number of years gives confidence in its performance. Example results are provided to illustrate the type of measurements which are possible.
Keywords: video photogrammetry; videogrammetry; 3d trajectories